2007
DOI: 10.1073/pnas.0700232104
|View full text |Cite
|
Sign up to set email alerts
|

Stress response during development predicts fitness in a wild, long lived vertebrate

Abstract: Short-term elevation of circulating glucocorticosteroids (GCs) in vertebrates facilitates the adoption of a distinct emergency life history state, which allows individuals to cope with perturbations and recover homeostasis at the expense of temporarily suppressing nonessential activities. Although GC responses are viewed as a major evolutionary mechanism to maximize fitness through stress management, phenotypic variability exists within animal populations, and it remains unclear whether interindividual differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
227
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 300 publications
(237 citation statements)
references
References 39 publications
3
227
2
5
Order By: Relevance
“…For example, fledgling Magellanic Penguins (Spheniscus magellanicus) showed no difference in baseline or stress-induced CORT across tourist and non-tourist visited areas [51] and Black-legged Kittiwake chicks (Rissa tridactyla) did not differ in their baseline or stress-induced CORT across levels of investigator disturbance [7]. R epeated exposure to stressors may have severe negative consequences on developing young such as suppression of growth [29] and reduced cognition [21] and even influence the probability of survival [4]. Thus the ability to maintain low baseline and stress-induced CORT in the face of environmental perturbations may act to minimize the deleterious effects of CORT on developing kestrels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, fledgling Magellanic Penguins (Spheniscus magellanicus) showed no difference in baseline or stress-induced CORT across tourist and non-tourist visited areas [51] and Black-legged Kittiwake chicks (Rissa tridactyla) did not differ in their baseline or stress-induced CORT across levels of investigator disturbance [7]. R epeated exposure to stressors may have severe negative consequences on developing young such as suppression of growth [29] and reduced cognition [21] and even influence the probability of survival [4]. Thus the ability to maintain low baseline and stress-induced CORT in the face of environmental perturbations may act to minimize the deleterious effects of CORT on developing kestrels.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental conditions can have significant effects on adult morphology, behavior, and physiology [26,4,28,10]. U ltimately, conditions experienced during development may impact growth, recruitment, reproduction, or survival that may in turn affect individual fitness and, perhaps, result in population changes [40,8,27,4,22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Blas et al [5] demonstrated that elevated responsiveness to a standardized stress protocol is negatively correlated with survival and recruitment in the European white stork (Ciconia ciconia). Other studies have demonstrated that environmental conditions and phenotypic manipulations affect the adrenocortical response to stress in developing birds.…”
Section: Investigator Handling Baseline Cort and Adrenoresponsivenessmentioning
confidence: 99%